Smart data in healthcare marketing: linking digital transformation to patient behavior and branding - Ashouri , Mohammad Farid; Tarassoli, Mehrdad (Social Determinants of Health, 2025)
Background: This study aimed to identify the key factors Influencing the application of smart technologies to improve patient communication, increase satisfaction, and strengthen brand image within the healthcare system Methods: This study employed a mixed-methods approach (qualitative–quantitative). In the qualitative phase, semi-structured interviews were conducted with 15 key informants, including hospital managers, digital health marketers, and AI/data specialists. Participants were selected through purposive. Thematic analysis was carried out using Braun and Clarke’s six-step framework. Coding was performed manually, and themes were validated through member checking and peer review. In the quantitative phase, data were collected using a structured questionnaire developed based on the themes identified in the qualitative stage. Path analysis and correlation tests were used to examine the relationships among variables. 200 participants were selected among hospital managers, health marketing specialists, and data analysts working in digital health settings.. Data analysis was conducted using SPSS version 23 and SmartPLS version 3. Results: Most experts validating the qualitative phase were male (62.5%), aged 30–40 (69%), held a master’s degree (77.5%), and had 5–10 years of experience (73%). Thematic analysis identified customer data analysis and content personalization as key AI-driven components in health marketing. Quantitative findings showed significant positive relationships between AI, advanced marketing, behavioral change, and branding strategies. Path analysis confirmed all hypotheses, with AI indirectly influencing branding via marketing and behavioral shifts. The model showed strong fit (GOF = 0.62) and acceptable reliability and validity. Conclusion: Integrating AI technologies into healthcare marketing not only improves patient experience but also enhances the branding position of healthcare organizations in competitive environments.